Political and Legal Representations of the Synergies between the State and the Religion - Alontseva, Dina V (2020)
The aim of the article is devoted to analyzing political and legal representations of the concepts of relations between two public institutions: the Church and the State, suggested by modern academics. Emphasis has been placed on the fact that the model of the religious and power synergy has been transformed by the existing system of values and is legally enshrined. The general dialectical scientific method enabled the authors to consider the problem of reformation of the religious legislation in the Russian Federation at the present stage; to demonstrate the changes in the religious legislation of the Russian Federation depending on a combination of internal and external factors affecting it. The results of the study let the authors draw the following conclusions:  the institution of religion in the modern world cannot avoid participation in settlement of political processes. Therefore, it is necessary to develop a mechanism for implementation of constitutional principles for the ties between the State and the Church.